KEBIJAKAN PENGGUNAAN BAHASA JURNALISTIK POPULIS PADA MEDIA CETAK DAN MEDIA ONLINE (STUDI DESKRIPTIF PADA PIKIRANRAKYAT DAN PIKIRAN-RAKYAT.COM) - Sudarjat, Muhammad Fauzaan Fikri Sudarjat; Muahemin, Enjang; khoirudin, Khoirudin (Jurusan Ilmu Komunikasi, Fakultas Dakwah dan Komunikasi, UIN Sunan Gunung Djati Bandung, 2022)
This study aims to find out how the policy of using populist journalistic language in the application and differences of writing in print media and online media Pikiran Rakyat. This research uses a qualitative approach with a constructivism paradigm, and a descriptive method. The results showed that in writing populist journalistic language in print and online media, the language used must be easily understood by various levels of society, including the poorly educated. The use of informal words and colloquial terms is characteristic, although it still refers to the Big Indonesian Dictionary (KBBI). The use of these words or terms can be found in various rubrics with the aim of attracting readers, and in some cases, absorptive language words that do not yet exist in KBBI are italicized as a reference for the editorial team. The main difference lies in print media that prioritize standard language over absorptive or foreign languages, while online media are more flexible in using populist journalistic language because it follows Search Engine Optimization (SEO) principles.